ESTIMATING HOUSE CONSTRUCTION COMPLETION TIME WITH PROBABILISTIC ACTIVITIES DURATION USING THE PROGRAM EVALUATION AND REVIEW TECHNIQUE (PERT) METHOD - Adnan Fadjar; Amar Akbar Ali; Arief Setiawan (Universitas Tadulako, 2023)
Construction housing projects involve many risks and uncertainties that can affect their completion time. To ensure a construction housing project is completed on time, an accurate duration estimate is required for each activity. Deterministic duration methods, such as the Critical Path Method (CPM), are commonly used in project scheduling for construction projects. However, this method may not always produce a realistic schedule as it uses only a single duration estimation for each activity. As an alternative, this study uses the Program Evaluation and Review Technique (PERT) which utilizes three duration estimates namely optimistic duration, most likely duration, and pessimistic duration. A house construction project with 23 activities was analyzed using CPM to find the critical activities which produced 59 days of completion time. The critical path duration was then analyzed using PERT. PERT calculations found that there was only a 15% probability to complete the project in 59 days, and the project needed 66 days of completion time with a 95% level of confidence. The findings of this study indicate that PERT can assist project managers in creating a more realistic project schedule by considering the risks and uncertainties in estimating the duration of its activities.